Dedicator of cytokinesis 8-deficient patients have a breakdown in peripheral B-cell tolerance and defective regulatory T cells - (:unkn) unknown (MOSBY-ELSEVIER, 2014)
Background: Dedicator of cytokinesis 8 (DOCK8) deficiency is typified by recurrent infections, increased serum IgE levels, eosinophilia, and a high incidence of allergic and autoimmune manifestations. Objective: We sought to determine the role of DOCK8 in the establishment and maintenance of human B-cell tolerance. Methods: Autoantibodies were measured in the plasma of DOCK8-deficient patients. The antibody-coding genes from new emigrant/transitional and mature naive B cells were cloned and assessed for their ability to bind self-antigens. RegulatoryT(Treg) cells in the blood were analyzed by means of flow cytometry, and their function was tested by examining their capacity to inhibit the proliferation of CD4(+)CD25(-) effector T cells. Results: DOCK8-deficient patients had increased levels of autoantibodies in their plasma. We determined that central B-cell tolerance did not require DOCK8, as evidenced by the normally low frequency of polyreactive new emigrant/transitional B cells in DOCK8-deficient patients. In contrast, autoreactive B cells were enriched in the mature naive B-cell compartment, revealing a defective peripheral B-cell tolerance checkpoint. In addition, we found that Treg cells were decreased and exhibited impaired suppressive activity in DOCK8-deficient patients. Conclusions: Our data support a critical role for DOCK8 in Treg cell homeostasis and function and the enforcement of peripheral B-cell tolerance.
Keywords: Dedicator of cytokinesis 8; autoimmunity; B-cell tolerance; regulatory T cells; DOCK8 DEFICIENCY; AUTOANTIBODY PRODUCTION; TRANSPLANTATION; EXPRESSION; LIGAND; LYMPHOCYTE; EXPANSION; PROFILES; REMOVAL; BAFF